Chemical composition and biological prospects of essential oils and extracts of aphyllocladus spartioides growing in northwest Argentina - Celaya, Liliana Soledad (2017)
Fil: Celaya, Liliana Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro de Investigaciones y Transferencia (Jujuy). Laboratorio de Productos Naturales del NOA; Argentina.